Enhanced Dry Process Method for Modified Asphalt Containing Plastic Waste - Radeef, Hasanain Radhi; Abdul Hassan, Norhidayah; Abidin, Ahmad Razin Zainal; Mahmud, Mohd Zul Hanif; Yusoffa, Nur Izzi Md.; Idham Mohd Satar, Mohd Khairul; Warid, Muhammad Naqiuddin Mohd (Frontiers in Materials, 2021)
In recent years, the proliferation of plastic waste has become a global problem. A potential option to this problem is the dry process, which incorporates plastic waste into asphalt mixtures. However, the dry process often has inconsistent performance because of the improper distribution of plastic waste particles in the mixture skeleton. This inconsistency may be caused by a wrong mixing method, shredding size, mixing temperature and ingredient priorities. Thus, this study aims to improve the consistency of the dry process by comparing the control asphalt mixture and two plastic waste-modified asphalt mixtures prepared using the dry process. Quantitative sieving analysis and performance tests were carried out to examine the effects of plastic waste added into the asphalt mixture. The volumetric and performance properties combined with image analysis of the modified mixtures were obtained and compared with the control mixture. In addition, the moisture damage, resilient modulus, creep deformation and rutting were evaluated. This study also highlighted in detail the distribution of plastic particles in the final skeleton of the asphalt mixture. Based on the analysis, an enhanced dry process of mixing procedure was proposed and evaluated. Results showed that the addition of plastic particles using the conventional dry process contributed a significant effect on the aggregate gradation of the produced mixture when a high plastic content was used. Furthermore, the enhanced dry process developed in this study presents substantial enhancement in the asphalt performance, particularly with plastic waste that accounts for 20% of the weight of the asphalt binder.